2010
DOI: 10.1182/blood-2010-04-280149
|View full text |Cite
|
Sign up to set email alerts
|

EZH2-mediated epigenetic silencing in germinal center B cells contributes to proliferation and lymphomagenesis

Abstract: EZH2 is the catalytic subunit of the PRC2 Polycomb complex and mediates transcriptional repression through its histone methyltransferase activity. EZH2 is upregulated in normal germinal center (GC) B cells and is implicated in lymphomagenesis. To explore the transcriptional programs controlled by EZH2, we performed chromatin immunoprecipitation (ChIP-onchip) in GC cells and found that it binds approximately 1800 promoters, often associated with DNA sequences similar to Droso-phila Polycomb response elements. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
250
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(259 citation statements)
references
References 43 publications
8
250
0
1
Order By: Relevance
“…Addition of these factors in clonogenic assays may enhance survival of human CD34 þ hematopoietic stem progenitor cells and increase size of hematopoietic colonies, in particular, in erythroid lineage. 2 However, Ins factors as reported may stimulate proliferation of leukemic blasts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of these factors in clonogenic assays may enhance survival of human CD34 þ hematopoietic stem progenitor cells and increase size of hematopoietic colonies, in particular, in erythroid lineage. 2 However, Ins factors as reported may stimulate proliferation of leukemic blasts.…”
mentioning
confidence: 99%
“…The PRC2/EZH2 complex binds to a specific set of target genes in germinal centre (GC) centroblasts, suggesting a GC-specific EZH2 regulatory programme in normal and malignant B cells. 2 Indeed, DNA-methylation profiling studies in FL by our group and others have shown that PRC2 gene targets in stem cells are significantly overrepresented among the hypermethylated genes in these tumours, linking these two epigenetic mechanisms in FL. 3 The spectrum of cancers with EZH2 mutation is also increasing, with mutations in myeloid disorders leading to reduced or complete loss of H3K27me3 expression consistent with a tumour suppressor role for EZH2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two epigenetic regulators (EZH2 and MOZ) involved in the histone modification were shown to play roles in the epigenetic changes involved in the formation of GCs (10)(11)(12)(13). Therefore, additional histone codes encoded by various epigenetic factors involved in the process are worth defining.…”
mentioning
confidence: 99%
“…EZH2 is a histone methyltransferase that functions as part of the polycomb group complex, which controls the balance between self-renewal and differentiation 49 . In germinal center (GC) B cells, EZH2 appears to suppress differentiation genes and favor behavior that resembles stem cells 50 . As in GC DLBCL cells, depletion of EZH2 in Bel/Fu hepatocellular carcinoma cells inhibited proliferation, but in Bel/Fu cells this depletion also increased methylation at the ABCB1 gene, reduced ABCB1 gene and protein expression 51 , and showed consequent sensitization of these cells to the cytotoxic effects of 5-fluorouracil 52 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%